Antiviral immunity of severe fever with thrombocytopenia syndrome: current understanding and implications for clinical treatment - Niu, Yuxin; Liu, Yunhui; Huang, Lanyue; Liu, Wei; Cheng, Qiuyu; Liu, Tingting; Ning, Qin; Chen, Tao (Frontiers in Immunology, 2024)
Dabie Banda virus (DBV), a tick -borne pathogen, was first identified in China in 2010 and causes profound symptoms including fever, leukopenia, thrombocytopenia and multi-organ dysfunction, which is known as severe fever with thrombocytopenia syndrome (SFTS). In the last decade, global incidence and mortality of SFTS increased significantly, especially in East Asia. Though previous studies provide understandings of clinical and immunological characteristics of SFTS development, comprehensive insight of antiviral immunity response is still lacking. Here, we intensively discuss the antiviral immune response after DBV infection by integrating previous ex -and in-vivo studies, including innate and adaptive immune responses, anti -viral immune responses and long-term immune characters. A comprehensive overview of potential immune targets for clinical trial s is provided as well. However, development of novel strategies for improving the prognosis of the disease remains on challenge. The current review may shed light on the establishment of immunological interventions for the critical disease SFTS.